1997
DOI: 10.1023/a:1012044526054
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cholic acid-amino acid conjugates with appropriate stereochemistry are recognized and transported by the human bile acid transporter and show modest HIV-1 protease inhibitory activity. Transport of these conjugates by the bile acid carrier is influenced by charge and hydrophobicity around the 24 position of the sterol nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…C-24 bile acid conjugates have previously been shown to be ASBT substrates (7,2931). One of these studies was a SAR study involving a series of C-24 cholic acid conjugates and found that the C-24 side chain can be 14 Å in length or longer for translocation, and that large hydrophobic moieties increase binding to ASBT (29).…”
Section: Resultsmentioning
confidence: 99%
“…C-24 bile acid conjugates have previously been shown to be ASBT substrates (7,2931). One of these studies was a SAR study involving a series of C-24 cholic acid conjugates and found that the C-24 side chain can be 14 Å in length or longer for translocation, and that large hydrophobic moieties increase binding to ASBT (29).…”
Section: Resultsmentioning
confidence: 99%
“…The splitting of proton resonances in the 1 H NMR spectra are defined as s = singlet, d = doublet, and m = multiplet. 13 C NMR spectra were recorded on a Varian 400 NMR spectrometer ( 13 C at 100.57). Peak positions shown are relative to tetramethylsilane.…”
Section: Generalmentioning
confidence: 99%
“…Bile acids comprise a large group of natural or semi-synthetic molecules that are readily available at low cost; they have been used for pharmaceutical purposes for a long time, because of their known value as drug carriers [13]. Bile acid transport in the gastrointestinal tract is recognized as being an efficient high capacity system because of its involvement in reabsorption of bile salts following fat digestion.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the ability of the human intestinal bile acid transporter to transport cholic acid conjugates with potential HIV-1 protease inhibitory activity, cholic acid was conjugated at the 24 position of the sterol nucleus with various amino acids and amino acid analogues such as 53 ( Fig. 12) [79]. In this study, one amino acid analog-cholic acid conjugate showed HIV-1 protease inhibitory activity.…”
Section: Steroid-amino Acid Conjugatesmentioning
confidence: 99%